Development of a practical guide for assessing infant motor development: contributions to teaching practice in early childhood education (Research, Society and Development, 2025)
Child motor development is a process through which children acquire and refine essential skills that enable them to interact with their environment and perform tasks across different contexts. In early childhood education, the systematic assessment of this process by teachers allows for the early identification of alterations that may influence overall development. The present study aimed to develop a practical guide for assessing infant motor development, offering teachers an effective tool to evaluate both typical motor development and identify warning signs of potential motor delays in early childhood education. This is a cross-sectional, quantitative study conducted in four Municipal Early Childhood Education Centers (CMEIs) in the city of Cascavel, Paraná (Brazil). Data collection was carried out through a semi-structured physical questionnaire completed by 31 teachers. The information was tabulated using Microsoft Excel® and analyzed descriptively. The results indicated that most participants possessed an intermediate level of knowledge regarding motor development, although they acknowledged the importance of ongoing training to enhance their assessment practices. It was also observed that a substantial proportion of the teachers did not use systematized assessment instruments, despite all of them expressing interest in adopting the proposed guide. These findings highlight the need for structured tools that support the observation, recording, and interpretation of children’s motor performance. The implementation of the Practical Guide for Functional Assessment has the potential to improve the evaluation process in early childhood education, promote the early detection of motor alterations, and guide more precise pedagogical interventions aligned with children’s needs.